Expression of anti-HBV primary micro-RNA shuttles using an inducible promoter system. - Mlambo, Tafadzwa (My University, 2014)
Hepatitis B virus (HBV) infection is an important global health concern and chronic carriers of the virus are at high risk of developing hepatocellular carcinoma (HCC) and cirrhosis. Current therapies are only partially effective, which emphasises the need for improved treatment strategies. Harnessing the RNA interference (RNAi) pathway as a treatment strategy against HBV has shown great promise. However, there are obstacles that need to be overcome before RNAi-based treatment of HBV infection is realised. These include problems of liver tissue targeting and dose regulation. This study investigated the use of a liver specific and mifepristone-inducible RNA polymerase (Pol) II promoter system for the specific and precise regulation of anti-HBV sequence expression. The inducible system used consists of two expression cassettes; one containing the regulator/transactivator protein and another containing the transgene. Natural primary microRNA (pri-miR) mimics, pri-miR-31/5 and pri-miR-31/5/8/9, were used as anti-HBV sequences. Firefly luciferase gene expression was used to test modulation by the inducible system and to determine optimal induction conditions. The pri-miR-31/5, pri-miR-31/5/8/9 and luciferase encoding fragments were incorporated into the plasmid vector pRS17 that bears the inducible promoter, creating pRS-31/5, pRS-31/5/8/9 and pRS-Luc respectively. Firefly luciferase expression with this system was shown to be inducible and mifepristone dose-dependent. Effective knockdown of HBV gene expression was achieved with both pRS-31/5 and pRS-31/5/8/9 in vitro and in vivo. However, with high vector amounts, similar efficiency in silencing of HBV gene expression was observed in the presence and absence of the inducer mifepristone suggesting leaky expression of the pri-miRs. To confirm this, knockdown studies were carried out with the pri-miR-31/5/8/9-expressing cassette separated from the transactivator cassette. HBV gene expression knockdown was observed with the pri-miR-31/5/8/9 cassette alone confirming leaky expression from the inducible system. Leakiness appears to be as a result of the E1B promoter driving the expression of the pri-miRs in the absence of mifepristone. However, reducing the vector amounts decreased basal expression and improved the inducibility of the system in cell culture studies. Successful propagation of an inducible and liver-specific RNAi-activating expression system will address the difficulty of achieving dose control of RNAi effectors and contribute to advancing the use of RNAi for HBV treatment.
Keywords: Hepatitis B Virus; RNA Interference